The concept of separate legal personality in company law and its impact on the governance of company groups - Maralack, Lawrence-John (University of the Witwatersrand, Johannesburg, 2023)
This research focuses on the concept of separate legal personality as it applies to company groups. This research analyses the phenomenon that the separate legal personality of subsidiaries within these company groups enables them to act in breach of good corporate governance norms. This is due to the fact that accountability may be avoided by the holding company in a group through the practice of ‘judgement proofing.’ This research proposes that a more progressive consideration of the remedy of piercing the corporate veil as well as finding alternatives to veil piercing can be used to ensure that the entity theory does not enable corporate malfeasance (as seen in the case of Milieudefensie vs Shell Petroleum Development Company of Nigeria Limited). It is argued that this will promote better corporate governance within company groups
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Legal personality; Company law; Company governance; UCTD; SDG-8: Decent work and economic growth